Comparison of the Suspended Sediment Dynamics in Two Loess Plateau Catchments, China. (23rd April 2017) - Zhao, Guangju; Yue, Xiaoli; Tian, Peng; Mu, Xingmin; Xu, Wenlong; Wang, Fei; Gao, Peng; Sun, Wenyi
Abstract: Changes in runoff and sediment loads are of great importance for the management of river basins and the implementation of soil and water conservation measures. This study compared the suspended sediment dynamics in the Huangfuchuan and Yanhe catchments on the Loess Plateau. Both annual runoff and sediment load displayed significant reductions from 1955 to 2012. The decreasing rates were −0·88 mm a −1 and −2·72 Mg ha −1  a −1 in the Huangfuchuan catchment, respectively, and ‐0.31 mm a −1 and −1·20 Mg ha −1  a −1 in the Yanhe catchment. A total of 183 and 195 events, respectively, were selected to assess the suspended sediment dynamics in both catchments during the periods of 1971–1989 and 2006–2012. The results showed a good linear relationship between the sediment yield and runoff depth in both catchments from 1971 to 1989 and a relatively worse relationship in the Yanhe catchment from 2006 to 2012. The magnitude and frequency of the hyper‐concentrated sediment flow obviously decreased in the 2000s compared with that between 1971 and 1989. A hysteresis analysis suggested that complex and counter‐clockwise loops were the dominant patterns. Various soil and water conservation measures (e.g., afforestation, grassing, terraces, and check dams) played a critical role in runoff and sediment load changes in both catchments. The two catchments showed obvious heterogeneities in runoff and sediment yield because of different lithologies, soil types, and vegetation. The results of this study provide valuable information on suspended sediment dynamics and could be used to improve soil erosion control measures on the Loess Plateau. Copyright © 2016 John Wiley & Sons, Ltd.